Access to harmonine, a chemical weapon of ladybird beetles - Philkhana, Satish Chandra; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Reddy, D. Srinivasa (RSC Advances, 2014)
The synthesis of harmonine, a defense alkaloid from the harlequin ladybird is reported by three different routes. The preparation of several new analogs with the same molecular weight and the decoration of gold nanoparticles with harmonines are also part of the present communication.